2021
DOI: 10.3390/ijerph18094850
|View full text |Cite
|
Sign up to set email alerts
|

Condom-Protected Sex and Minority Stress: Associations with Condom Negotiation Self-Efficacy, “Passing” Concerns, and Experiences with Misgendering among Transgender Men and Women in Brazil

Abstract: This cross-sectional exploratory study aims to verify associations between condom-protected sex, condom negotiation self-efficacy, self-esteem, and four minority stressors (experiences with misgendering, “passing” concerns, anticipated prejudice, and perceived prejudice) among transgender men (TM) and transgender women (TW). 260 individuals (192 TW and 68 TM) residing in two Brazilian states participated in the study. Data was collected online and in two hospital programs for transgender people and included so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…All eight items demonstrated high factor loading in a one‐factor construct which explained 65% of the variance in the Ontario sample [ 18 ]. Similar to previous studies [ 18 , 21 ], the internal consistency of the T‐Barrier Scale in the current dataset was high (Cronbach's α = 0.92).…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…All eight items demonstrated high factor loading in a one‐factor construct which explained 65% of the variance in the Ontario sample [ 18 ]. Similar to previous studies [ 18 , 21 ], the internal consistency of the T‐Barrier Scale in the current dataset was high (Cronbach's α = 0.92).…”
Section: Methodssupporting
confidence: 89%
“…For instance, Trans PULSE did not detect significant gendered differences between AFAB and AMAB groups [ 18 ] and a Brazilian study reported a higher perceived ability to negotiate protective barriers (e.g. condoms) among trans men than trans women [ 21 ]. Our study asserted the importance of examining the intersection of gender and sexual attraction, as we only found significant gendered differences among those attracted to men: trans women had higher certainty around negotiating protective barrier use than trans men and non‐binary AFAB people.…”
Section: Discussionmentioning
confidence: 99%
“…The high circulation of HIV among TGW-SW cannot be only and simply explained by high rates of risky sexual behaviours, such as unprotected receptive anal intercourse. Social marginalisation, lack of control on life and sexuality, low self-esteem, difficult access to healthcare, legal problems, stigma, discrimination, violence, mental illnesses and substance abuse are all intertwined factors that contribute to increasing the risk of HIV acquisition 14–17. In this respect, collection of behavioural information is important to identify specific health needs and to individualise diagnostic and preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Few interventional studies have measured condom use; however, the studies used a wide range of measures and showed mixed results [ 7 , 8 , 19 , 20 , 21 ]. For instance, a study done in Nigeria found similar results when compared with the control group [ 19 ].…”
Section: Discussionmentioning
confidence: 99%